Inhibition of extracellular signal‐regulated kinases 1/2 provides neuroprotection in spinal cord ischemia/reperfusion injury in rats: relationship with the nuclear factor‐κB‐regulated anti‐apoptotic mechanisms - Lu, Kang; Liang, Cheng‐Loong; Liliang, Po‐Chou; Yang, Chih‐Hui; Cho, Chung‐Lung; Weng, Hui‐Ching; Tsai, Yu‐Duan; Wang, Kuo‐Wei; Chen, Han‐Jung (Journal of neurochemistry, 2010)
J. Neurochem. (2010) 114, 237–246. Previously we demonstrated benefits of inhibiting the extracellular signal‐regulated kinases 1/2 (ERK1/2) signaling pathway in spinal cord ischemia/reperfusion (I/R) injury. To further identify the underlying mechanisms, we investigated the impact of ERK inhibition on apoptosis and cellular protective mechanisms against cell death. Spinal cord I/R injury induced ERK1/2 phosphorylation, followed by neuronal loss through caspase 3‐mediated apoptosis. Pre‐treatment with U0126, a specific inhibitor of MAPK/ERK kinases 1/2 (MEK1/2), inhibited ERK1/2 phosphorylation, and significantly attenuated apoptosis and increased neuronal survival. MEK/ERK inhibition also induced I‐κB phosphorylation and enhanced nuclear factor (NF)‐κB/DNA binding activity, leading to expression of cellular inhibitors of apoptosis protein 2 (c‐IAP2), a known nuclear factor‐κB (NF‐κB)‐regulated endogenous anti‐apoptotic molecule. Pyrrolidine dithiocarbamate, an NF‐κB inhibitor, by blocking I‐κB phosphorylation, NF‐κB activation, and c‐IAP2 synthesis, abolished the protective effects of U0126. The MEK/ERK pathway appears to mediate cellular death following I/R injury. The U0126 neuroprotection appears related to NF‐κB‐regulated transcriptional control of c‐IAP2. MEK/ERK inhibition at the initial stage of I/R injury may cause changes in c‐IAP2 gene expression or c‐IAP2/caspase 3 interactions, resulting in long lasting therapeutic effects. Future research should focus on the possible cross‐talk between the MEK/ERK pathway and the NF‐κB transcriptional cascade.